Image-based assessment of tail docking and tail biting in slaughtered pigs across three European countries - Romano, Anastasia; Baghini, Simona; Capobianco Dondona, Andrea; Bernabò, Nicola; Marruchella, Giuseppe (Frontiers in Veterinary Science, 2026)
Slaughterhouse monitoring provides a cost-effective and suitable tool for large-scale surveillance of tail-biting, which is a major welfare issue in pig production. The European Union Council Directive 2008/120/EC prohibits routine tail-docking as a preventive measure against tail-biting. Nevertheless, compliance remains inconsistent, and tail-docking is still widely practiced in Europe. This study aimed to assess the occurrence of tail-biting and tail-docking in slaughtered pigs (n = 15,000) from Italy, Netherlands and Spain using digital images. Results indicate that most pigs were tail-docked (88.1%), with substantial variation among countries: tail-docking was most common in Spain (99.4%), followed by Netherlands (86.5%), and least common in Italy (78.5%). Overall, tail-biting lesions were observed in 5.4% of pigs, with the highest prevalence in Italy (11.6%), followed by Netherlands (3.4%), and Spain (1%). The differences among the three countries were significant (p < 0.0001), tail lesions being more frequent in pigs with undocked tails than docked tails (p < 0.0001). The risk of having a lesion was substantially higher in pigs with undocked/intermediate tails (relative risk = 4.6). The severity of lesions was scored using two different methods, which showed an almost perfect agreement (weighted Cohen’s kappa coefficient 0.826; p < 0.0001). Lesions were most frequently detectable in the two lateral views, whereas the central view alone was inconclusive in most of pigs (99%).